Fatty Acids/Tetraphenylethylene Conjugates: Hybrid AIEgens for the Preparation of Peptide-Based Supramolecular Gels - Elisa Impresari; Alberto Bossi; Alberto Bossi; Edoardo Mario Lumina; Marco Aldo Ortenzi; Josine Marie Kothuis; Graziella Cappelletti; Daniela Maggioni; Michael S. Christodoulou; Raffaella Bucci; Sara Pellegrino (Frontiers in Chemistry, 2022)
Aggregation-induced emissive materials are gaining particular attention in the last decades due to their wide application in different fields, from optical devices to biomedicine. In this work, compounds having these kinds of properties, composed of tetraphenylethylene scaffold combined with fatty acids of different lengths, were synthesized and characterized. These molecules were found able to self-assemble into different supramolecular emissive structures depending on the chemical composition and water content. Furthermore, they were used as N-terminus capping agents in the development of peptide-based materials. The functionalization of a 5-mer laminin-derived peptide led to the obtainment of luminescent fibrillary materials that were not cytotoxic and were able to form supramolecular gels in aqueous environment.